Selected Aspects Related to Preparation of Fatigue Tests of a Metallic Airframe - Brzęczek Józef; Chodur Jerzy; Pietruszka Janusz (Fatigue of Aircraft Structures, 2014)
The basis for the computation of the service life of the PZL M28 was the results of the full-scale fatigue tests of the structure [1]. As the PZL M28 is a commuter category airplane according to the 14 CFR Part 23 and CS-23 regulations, the test objects were: (1) wing and wing load carry-through structure, (2) empennage and attached fuselage structure. Additionally, there were fatigue tests carried out for the landing gear and other selected elements including control system elements. The aircraft load carry-through structure is metallic and the cabin is unpressurized. The fatigue tests were conducted stage-by-stage. As the tests progressed, it was possible to extend the aircraft’s target service life, applying a safe life philosophy with reference to the primary components of the load carry-through structure.